PENGARUH CELEBRITY ENDORSER, CITRA MEREK, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SHAMPO PANTENE (studi komparatif antara kelompok usia remaja dan dewasa di Kota Pontianak) - B31112014, HERI SUHENDA (Jurnal Manajemen Update, 2016)
During 2011 Indonesian women have used the products Pantene and also Pantene excels in the Best Brand Award (Ibba) in 2011, while the PT. Procter & Gamble Indonesia was established in 1989 in Indonesia P&G market shampoo brand Pantene Rejoice and Head&Shoulders, Currently shampoo Pantene has four variants, namely anti dandruff, total care, hair fall, smooth and silky. This study aims to determine: (1) To test and analyze the differences in the responses of Celebrity Endorser, Brand Image, Product Quality and Purchasing Decision Pantene Shampoo by groups of respondents adolescents and adults. (2) To examine and analyze the effect of Celebrity Endorser on product purchasing decisions Shampoo Pantene in Pontianak. (3) To examine and analyze the effect on purchase decisions Brand Image Shampoo Pantene products in Pontianak. (4) To examine and analyze the effect on purchasing decisions Quality Products Shampoo Pantene products in Pontianak. This study uses comparative research design and causal design, while the population of this study consumer purchase decision makers and users of Pantene shampoo in Pontianak. Technique sampling the used in this research is purposive sampling, while the sample in this study amounted to 100 respondents were divided into two groups of samples that age group and older age groups who are users of Pantene shampoo in Pontianak. Analyzer used different test t-test and then multiple regression analysis by first tested the validity, reliability and classic assumption. The results showed that there was no difference in response between the age group of adolescent and adult age groups on purchasing decisions shampoo Pantene, then the third variables such as celebrity endorser,brand image and product quality and significant positive influence on purchasing decisions pantene shampoo in the city of pontianak. Keywords: celebrity endorser, brand image, product quality, purchasing decisions.